IS KNOWLEDGE OF A NON!DOMINANT L2 ACTIVATED BY BILINGUALS USING THEIR DOMINANT L1? INSIGHTS FROM AN ON!LINE PSYCHOLINGUISTIC STUDY - de Souza, Ricardo Augusto; de Oliveira, Fernando Luiz (Organon, 2011)
L1 influences on L2 learning and use are phenomena vastlydocumented in L2 learning research (ODLIN, 1989; JARVIS & PAVLEN-KO, 2007). However, approaches to the inversed phenomenon, i.e.: L2 influences on L1, are more recent (COOK, 2003). Studies of L2 e" ectson the L1 tend to examine bilinguals living in the linguistic environmentsof the L2. In the present study, we report the results of a psycholinguis-tic study that suggests that bilinguals who probably have their L1 as thedominant language may nonetheless activate L2 semantics-syntax inter-face representations over the course of sentence processing. We discussour results with respect to their implications for the cognitive architectureof bilinguals’ language representations, as well as what they might signifyfor language contact situations.